Labour turnover and the spatial distribution of unemployment: A panel data analysis using employment registry data - Francesco Pastore; Joanna Tyrowicz (Institute for the Study of Labor (IZA), 2012)
This paper aims to study whether the local variation in unemployment rates is related to labour turnover and what is the sign of such relationship. In addition, the paper aims to assess the relative impact of inflow and outflow from unemployment on the dynamics of the local unemployment rate. The empirical analysis is based on a newly available unique dataset from the employment registry of a transition economy (Poland), encompassing nine years of monthly data (from 2000 to 2008) at a county (poviat) level. We find that turnover, as well as inflows and outflows separately, are ceteris paribus positively related to the unemployment level. This general conclusion is robust to sub-sampling that addresses potential heterogeneity of the analysed local labour markets. It is also robust to the use of different panel estimators as well as for spatial clustering of poviats. We also find that elasticity is larger in the case of the inflow rate than for the outflow rate. Finally, we demonstrate that the effect is stronger in low unemployment regions.
Keywords: C33; J63; P25; P52; R23; 330; regional unemployment; labour turnover; panel data; Poland; Regionale Arbeitslosigkeit; Arbeitsmobilität; Regionaler Arbeitsmarkt; Schätzung; Polen